Acetylcarnitine, carnitine and glucose diminish the effect of muscarinic antagonist quinuclidinyl benzilate on striatal acetylcholine content - Rícný, J; Tucek, S; Nováková, J (Brain research, 1992)
The content of acetylcholine (ACh) in the striatum, brain cortex and hippocampus of rats was lowered 20-180 min after intraperitoneal injection of the muscarinic antagonist quinuclidinyl benzilate (QNB). The depletion of ACh content in the striatum was diminished in animals treated with a single dose of acetyl-L-carnitine, L- or D,L-carnitine, or D-glucose. It is likely that QNB stimulates ACh release by blocking presynaptic muscarinic autoreceptors and that acetylcarnitine, carnitine and glucose support the resynthesis of ACh by increasing the availability of acetylcoenzyme A. They do not have the same consistent effect in the brain cortex and hippocampus; this difference may be related to the lower turnover rate of ACh and to the difference in the anatomical arrangement of cholinergic structures in these parts of the brain.
Keywords: Animals; Rats; Female; hipokampus; chinuklidinylbenzilát; Kinetics; inbrední kmeny potkanů; ženské pohlaví; corpus striatum; Acetylcarnitine; acetylcholin; Corpus Striatum; karnitin; Rats, Inbred Strains; Quinuclidinyl Benzilate; Male; acylkarnitin; glukosa; Acetylcholine; Glucose; krysa rodu Rattus; Hippocampus; mozková kůra; Cerebral Cortex; zvířata; mužské pohlaví; Carnitine; kinetika